Anomalous piezoelectric properties of poly(vinylidene fluoride–trifluoroethylene)/ionic liquid gels. (19th February 2018) - Fukagawa, Miki; Koshiba, Yasuko; Fukushima, Tatsuya; Morimoto, Masahiro; Ishida, Kenji
Abstract: Piezoelectric gels were prepared from low-volatile ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([Emim][TFSI]) gels, and their structural, ferroelectric, and piezoelectric properties were investigated. Poly(vinylidene fluoride–trifluoroethylene) P(VDF–TrFE)/IL gels were formed using thermally reversible physical gels. The structural characterization indicated that the P(VDF–TrFE) molecules in the gels predominantly formed a ferroelectric phase (Form I) of P(VDF–TrFE). Polarization switching peaks were clearly observed using a three-layer stacked device structure. The coercive field of the P(VDF–TrFE)/IL gels substantially decreased to 4–9 MV/m, and their remnant polarizations were maintained at 63–71 mC/m 2, which is similar to that for typical solid-state P(VDF–TrFE). Finally, the P(VDF–TrFE)/IL gel films exhibited a piezoelectric response, and the highest piezoelectric coefficient was ∼300 pm/V at an applied voltage frequency of 4 kHz.